ACCOUNTING AND ANALYTICAL SUPPORT OF THE FARMING DEVELOPMENT MANAGEMENT: THEORETICAL ASPECTS - Prokopyshyn О.; Pryimak Н.; Trushkina Н.; Konoval М. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
In the current stage, due to the influence of globalization and European integration on Ukraine's national economy, there is a clear need to develop significantly new mechanisms for accounting and analytical management of farms' development. The article explains the theoretical principles of forming accounting and analytical support for managing farming development. Using a systematic approach and a classification method, the interpretation of the term "accounting and analytical support" proposed by various scientific schools is categorized into groups such as: system, activity, process, management function, information system, integrated information support system, interactive structure, a set of accounting and analytical processes, etc. The authors propose a conceptual model for defining the concept of "accounting and analytical support for the management of agricultural development." This model consists of interconnected accounting and analytical procedures and is designed to provide the enterprise management team with necessary information. It relies on operational, statistical, financial, and management accounting data, as well as statistical, production, reference, and other types of information, digital technologies, and intelligent systems for economic analysis. It is a system for gathering, summarizing, and transmitting information that informs management decisions and aids in the planning and control of farm activities and development. The text outlines the key principles for creating accounting and analytical support for managing the development of farming. These principles encompass various aspects such as purposefulness, initiative, systematicity, structuredness, maneuverability, alternative opinions, multivariateness, reliability, objectivity, timeliness, continuity, efficiency, flexibility, reasonableness, feedback, and hierarchy. They are organized into groups including normative and legal regulation, general scientific principles, accounting principles (financial statements, financial accounting, tax accounting, management accounting, accounting organization, automated accounting), and economic analysis principles (industry principles, analysis of economic activity, financial analysis, strategic analysis, mathematical and statistical analysis). Furthermore, a structural and logical scheme for accounting and analytical management of farm development has been developed. Implementing this scheme will aid in making timely and scientifically informed management decisions, particularly in crises, regarding the strategic development of farms.